2023
DOI: 10.1186/s12967-023-04306-0
|View full text |Cite
|
Sign up to set email alerts
|

The effects of probiotics supplementation on glycaemic control among adults with type 2 diabetes mellitus: a systematic review and meta-analysis of randomised clinical trials

Abstract: Objective This systematic review and meta-analysis study aimed to evaluate the effectiveness of probiotics supplementation on glycaemic control in patients with type 2 diabetes mellitus (T2DM) based on the data from the randomised clinical trials (RCTs). Methods PubMed, Web of Sciences, Embase, and Cochrane Library were searched from the inception to October 2022, and RCTs about probiotics and T2DM were collected. The standardised mean difference (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In contrast, pooling data more broadly may be appropriate if the aim is more exploratory, for example, investigating a common mechanism of action that might be expressed across larger taxonomic groups. Underlying characteristics may be shared among taxonomic groups at a species or genus level that drive equivalent efficacy for a shared mechanism of action …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, pooling data more broadly may be appropriate if the aim is more exploratory, for example, investigating a common mechanism of action that might be expressed across larger taxonomic groups. Underlying characteristics may be shared among taxonomic groups at a species or genus level that drive equivalent efficacy for a shared mechanism of action …”
Section: Resultsmentioning
confidence: 99%
“…A total of 778 articles were identified by the literature search and 183 probiotic SRMAs were pulled for screening, along with 23 additional studies provided by panel members (total of 206 SRMAs) (Figure 2). A total of 42 representative examples for 11 disease conditions were selected: prevention of antibiotic-associated diarrhea (AAD) (n = 7), [33][34][35][36][37][38][39] treatment of irritable bowel syndrome (n = 9), [40][41][42][43][44][45][46][47][48] treatment of pediatric acute gastroenteritis (n = 10), [49][50][51][52][53][54][55][56][57][58] prevention of postsurgical infections (n = 3), [59][60][61] treatment of atopic dermatitis (n = 3), [62][63][64] prevention of respiratory tract infections (n = 2), 65,66 prevention of neonatal infections (n = 2), 67,68 and mechanistic studies for diabetic metabolism (n = 3), [69][70][71] immune regulation (n = 1), 72 mental health (n = 1), 73 or weight loss (n = 1). 74…”
Section: Literature Review Of Issuesmentioning
confidence: 99%
“…Bifidobacterium species are widely recognized as crucial contributors to infant health, particularly during the first 6 months of life when exclusive breastfeeding is prevalent, as they play a significant role in immune system development [51,52]. While Bifidobacterium species have acted as probiotics, demonstrating the ability to reduce fasting blood glucose levels and alleviate insulin resistance across various study populations [53], it is worth noting that prior research on type 2 diabetes (T2D) has identified an increase in Bifidobacterium taxa within the gut microbiota of patients [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Dutch adults, it was found that high abundance of butyrate-producing bacteria, including Clostridiaceae 1, Lachnospiraceae, C sensu stricto 1, Intestinibacter , and Romboutsia , is associated with a lower risk of T2DM ( 139 ). By colonizing the gut microbiota or supplementing with probiotics, insulin resistance, body mass index, and gut microbiota composition in T2DM patients can be significantly improved ( 140 , 141 ). A randomized, double-blind, placebo-controlled trial found that a combination probiotic, Probio-X (composed of Lactobacillus casei LCZ, Lactobacillus plantarum P-8, Lactobacillus rhamnosus Probio-M9, Lactobacillus paracasei Probio-M8 , and Lactobacillus paracasei V9 ), can enhance the therapeutic effect of metformin in T2DM by promoting the production of short-chain fatty acids and the bile acid pathway ( 142 ).…”
Section: Dysbiosis Of the Gut Microbiota Can Lead To Metabolic Disordersmentioning
confidence: 99%